Improvement and Evaluation of a Heuristic Method for the Minimal Feedback Arc Set Problem - Pustoslemšek, Jure; Črne, Ema; Rihter, Nejc (Proceedings of the10th Student Computing Research Symposium (SCORES’24), 2024)
This paper addresses the problem of finding minimal feedback arc sets in directed graphs, a critical issue in various domains such as computational biology, scheduling and network analysis. We implement, analyse and improve a novel heuristic approach. Our improved method reuses their heuristic method for reducing solu-tion size and uses other established techniques from both exact and approximate algorithms to speed up the algorithm. The implemen-tation makes use of a fast network analysis library for additional speed-up.